Studies on the Removal of Sr(II) Ions from Water Using Carbonized Orange Juice Residue - Paudyal, Hari; Pangeni, Bimala; Basnet, Prabin; Inoue, Katsutoshi (International Journal of Environment, 2021)
The adsorbent for Sr(II) ion removal was prepared from orange juice residue (OJR) after carbonization at 800°C. An energy dispersive X-ray (EDX) spectroscopic analysis showed the existence of trace amounts of P, Na, K, and Fe together with C and Ca in the examined sample of COJR. The adsorption parameters such as effect of pH, contact time, initial Sr(II) concentration and adsorbent dosage were studied. COJR selectively adsorbed Sr(II) from the mixed solution containing Sr(II) and Cs(I). Experimental data obtained for the adsorption of Sr(II) were analyzed by using Langmuir and Freundlich isotherm models, and the data were well fitted with both the models with R2 higher than 0.98. Adsorption equilibrium was achieved within one hour by using a 24.3 mg/L Sr(II) solution at a solid-liquid ratio of 1g/L. The maximum adsorption capacity (Qmax) and adsorption equilibrium constant (b) of COJR for Sr(II) ion were found to be 322.58 mmol/kg and 1.93 L/mmol, respectively. The concentration of Sr(II) was successfully lowered down to the EPA standard (4 mg/L) by using COJR dosage higher than 4 g/L. The adsorbed Sr(II) could be successfully desorbed using a dilute (0.5M) solution of hydrochloric acid. These results indicated that COJR investigated in this study showed a high affinity for Sr(II) ion thus it is expected to be employed as a promising adsorbent for the removal of Sr(II) ions from polluted water.